Faster efficacy and reduced nodule occurrence with PLLA (poly-l-lactic acid) porous microspheres - Cao, Qihua; Chen, Jiayu; Zhang, Zijun; Xiong, Yufei; Ma, Jinxia; Sun, Wei; Chen, Xin; Lou, Qilei; Tang, Kaijia; Lin, Feng; Zhu, Yueliang; Yu, Xiaohua (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionPoly-L-lactic acid (PLLA) has gained prominence as an injectable dermal filler as it can both stimulate collagen regeneration and deliver long-lasting effects. However, its application is often hampered by delayed therapeutic onset and adverse events, particularly nodule formation, likely due to uneven distribution caused by the easy formation of small clumps during PLLA reconstitution.MethodsIn this study, PLLA porous microspheres were administered at six dorsal sites on one flank of New Zealand white rabbits, with six contralateral sites receiving Löviselle as control. At predetermined experimental time points, subjects were humanely euthanized. Post-euthanasia, tissue sections underwent histological examination through hematoxylin and eosin (H&E) staining and Masson’s trichrome technique, with subsequent statistical analysis of the observational data.ResultsThe PLLA porous microsphere group demonstrated significantly faster onset of action compared to the control, with observable collagen deposition as early as week 2, enhanced inflammatory cell infiltration, more homogeneous tissue distribution, and substantially fewer microaggregates upon histological examination.DiscussionStructural modification of PLLA microspheres has successfully accelerated their onset of action while reducing nodule formation, thereby providing novel insights for clinical applications.